MENIMBA PENGHARAPAN DARI PENDERITAAN TAFSIRAN IMAN ATAS RATAPAN YEREMIA 3 AYAT 31–33 TENTANG KASIH SETIA ALLAH YANG TAK PERNAH BENAR-BENAR PERGI - Wilda Rupang (Adisam Publisher, 2026)
This article examines the theological significance of Lamentations of Jeremiah 3:31–33 by highlighting God's faithful love amidst the people's suffering. The text of Lamentations of Jeremiah arose from the context of the destruction of Jerusalem, which created a crisis of faith, social, and spirituality for the people of Judah. ​​In this situation, suffering is easily understood as a sign of God's rejection and absence. However, through a theological study of Lamentations of Jeremiah 3:31–33, this article shows that God's rejection is not eternal, His mercy continues to operate amidst hardship, and He does not desire to oppress humanity. This research uses a qualitative approach with library methods and theological hermeneutic interpretation of relevant Indonesian-language Bible texts and Old Testament literature. The results of the study indicate that the suffering in Lamentations of Jeremiah does not negate the covenant relationship between God and His people, but rather becomes a space for profound reflection on faith. God's faithful love is understood as a reality that transcends the subjective experience of suffering and becomes the basis for mature and realistic hope. This article emphasizes that true faith does not avoid lamentation but instead finds hope in it.